Betulinic Acid Derivative BA5, Attenuates Inflammation and Fibrosis in Experimental Chronic Chagas Disease Cardiomyopathy by Inducing IL-10 and M2 Polarization - Meira, Cássio Santana; Santos, Emanuelle De Souza; Santo, Renan Fernandes do Espírito; Vasconcelos, Juliana Fraga; Orge, Iasmim Diniz; Nonaka, Carolina Kymie Vasques; Barreto, Breno Cardim; Caria, Alex Cleber Improta; Silva, Daniela Nascimento; Barbosa-Filho, José Maria; Macambira, Simone Garcia; Moreira, Diogo Rodrigo Magalhães; et al. (Frontiers in Immunology, 2019)
Chronic Chagas disease cardiomyopathy (CCC) is a major cause of heart disease in Latin America and treatment for this condition is unsatisfactory. Here we investigated the effects of BA5, an amide semi-synthetic derivative betulinic acid, in a model of CCC. Mice chronically infected with T. cruzi were treated orally with BA5 (10 or 1 mg/Kg), three times per week, for two months. BA5 treatment decreased inflammation and fibrosis in heart sections but did not improve exercise capacity or ameliorate cardiac electric disturbances in infected mice. Serum concentrations of TNF-α, IFN-γ and IL-1β, as well as cardiac gene expression of pro-inflammatory mediators, were reduced after BA5 treatment. In contrast, a significant increase in the anti-inflammatory cytokine IL-10 concentration was observed in BA5-treated mice in both tested doses compared to vehicle-treated mice. Moreover, polarization to anti-inflammatory/M2 macrophage phenotype was evidenced by a decrease in the expression of NOS2 and proinflammatory cytokines and the increase in M2 markers, such as Arg1 and CHI3 in mice treated with BA5. In conclusion, BA5 had a potent anti-inflammatory activity on a model of parasite-driven heart disease related to IL-10 production and a switch from M1 to M2 subset of macrophages.